(3eONd JMdjdj hJWHjbjs - (3SYjO YHO GdYRjR(B, (3YKeGfs ((3GdGScfOQjI(B:s (3ecJHI heWHYI GdGTYGY GdafjI(B,s)
(3GdEWGQ GdYGe ddefXeI GdVQjHjI, OhQ GdfXGe GdVQjHj aj JMbjb CgOGa GdeLJeY, OhQ GdfXGe GdVQjHj aj JMbjb YOGdI JhRjY GdONd, GdfXGe GdVQjHj GdCeQjcj, GdfXGe GdVQjHj GdeUQjs
Keywords: (3GdVQjHIs; (3GdeLJeYs